Rasional Penggunaan Obat Ains Pada Pasien Rematik Osteorthritis Rawat Jalan Di Puskesmas Singosari Kota Pematangsiantar Periode Januari-Februari 2019 - Ismi Noer Fadilah; Hendri Kurniawan; Marthalea Erbin Nahak; Bernido Raflo Purba; Muharti Sanjaya; Dilla Sastia Mara (Jurnal Kesehatan, 2020)
The aim of the study was to determine the rationality of the accuracy of the diagnosis, the accuracy of the indication, the accuracy of the drug, the accuracy of the dose, the correct patient and the accuracy of the administration of NSAIDs in patients with rheumatic osteoarthritis so that no adverse effects occur. This research was carried out on outpatients at the Singosari Health Center, Pematangsiantar City for the January-February 2019 period. Research data collection was carried out in July 2019. The results showed that Rationality in terms of 6 accuracy (right diagnosis, right indication, right drug, right dose, right route of administration, right patient) then the results of the analysis show that accuracy is 100% right, while for the right drug parameters it is still worth 53% . So it can be concluded that treatment for Osteoarthritis patients when viewed from the right diagnosis, right indication, right dose, right patient, right drug, right method of administration at the Singosari Health Center cannot be fully rational.